The Parametric Analysis of the Supported Circular Working Interacting with the Layered Massif - Alkhdour, Ahmad M.; Radkevych, Anatolii V.; Tiutkin, Oleksii L.; Bondarenko, Nataliia (IOP Publishing Ltd, 2022)
ENG: The underground construction is based on effective and rapid building of running tunnels that connect stations. The most effective technique of building is shield-driven tunneling. It is based on the application of a tunneling shield, it means, a special aggregate that excavates the ground and builds support. Even with the fact that it holds a surrounding massif, in the weak and layered rocks it is possible the formation of subsidence trough, namely, significant deformations of the daylight area. The solution of this geomechanical problem is possible on the basis of the parametric analysis of the supported circular working interacting with a layered massif. The results of the parametric analysis allow to predict deformation in the "tunneling shield – support of tunnel – surrounding massif" system. For the parametric analysis, the authors use a numerical method of finite elements based on the complex Structure Computer-Aided Design. The calculations of six supported workings with a variation of the properties of a layered massif are carried out. The results of the stress-strain state allow introducing the matrix of parameters into the prediction calculations, enabling quickly and effectively analyze the possible change in the material of support and provide recommendations for the technology of shield-driven tunneling.

UKR: Будівництво метрополітенів базується на ефективному та швидкому спорудженні перегінних тунелів, що сполучають станції. Найбільш ефективною технологією спорудження є щитова проходка. Вона заснована на застосуванні прохідницького щита, тобто спеціального агрегату, що розроблює ґрунт та споруджує оправу. Навіть при тому, що він утримує оточуючий масив, в слабких та шаруватих породах можливе утворення мульди осідання, тобто значних деформацій денної поверхні. Вирішення цієї геомеханічної задачі можливе на основі параметричного аналізу закріпленої колової виробки, що взаємодіє з шаруватим масивом. Результати параметричного аналізу дозволяють прогнозувати деформування системи «прохідницький щит – оправа перегінного тунелю – оточуючий масив». Для проведення параметричного аналізу був застосований чисельний метод скінченних елементів на основі програмного комплексу StructureCAD (SCAD). Були проведені розрахунки шести закріплених виробок із варіацією властивостей шаруватого масиву. Отримані результати напружено-деформованого стану дозволили увести в прогнозні розрахунки матрицю параметрів, що дозволяє швидко та ефективно аналізувати можливу зміну матеріалу оправи та надавати рекомендації щодо технології щитової проходки.
Параметричний аналіз закріпленої кругової виробки, що взаємодіє з шаруватим масивом
O. Tiutkin: ORCID 0000-0003-4921-4758; A. Radkevych: ORCID 0000-0001-6325-8517; A. Alkhdour: ORCID 0000-0002-4148-5994
Keywords: the parametric analysis; circular working; layered massif; щитова проходка; закріплена горизонтальна виробка; параметричний аналіз; шаруватий масив; напружено-деформований стан; КТІ; КБВ